Overnight olfactory enrichment using an odorant diffuser improves memory and modifies the uncinate fasciculus in older adults - Woo, Cynthia C.; Miranda, Blake; Sathishkumar, Mithra; Dehkordi-Vakil, Farideh; Yassa, Michael A.; Leon, Michael (Frontiers in Neuroscience, 2023)
Objective Cognitive loss in older adults is a growing issue in our society, and there is a need to develop inexpensive, simple, effective in-home treatments. This study was conducted to explore the use of olfactory enrichment at night to improve cognitive ability in healthy older adults. Methods Male and female older adults (N = 43), age 60–85, were enrolled in the study and randomly assigned to an Olfactory Enriched or Control group. Individuals in the enriched group were exposed to 7 different odorants a week, one per night, for 2 h, using an odorant diffuser. Individuals in the control group had the same experience with de minimis amounts of odorant. Neuropsychological assessments and fMRI scans were administered at the beginning of the study and after 6 months. Results A statistically significant 226% improvement was observed in the enriched group compared to the control group on the Rey Auditory Verbal Learning Test and improved functioning was observed in the left uncinate fasciculus, as assessed by mean diffusivity. Conclusion Minimal olfactory enrichment administered at night produces improvements in both cognitive and neural functioning. Thus, olfactory enrichment may provide an effective and low-effort pathway to improved brain health.